ELECTRICAL CONDUCTIVITY AND ACCELERATED AGEING TECHNIQUES FOR EVALUATING DETERIORATION IN CUCURBITACEOUS VEGETABLES - L., CHITRA DEVI; Sharma, D.K.; KAK, ANJALI; Gupta, VEENA; PANDEY, SUSHIL (Annals of Agricultural Research, 2014)
Three promising varieties of Bottle gourd, Sponge gourd and Round melon of cucurbitaceous vegetables were artificially aged at 450C and 100 per cent relative humidity for 9 days. The experimental results revealed that accelerated ageing showed significant effect on loss of germination per cent, seedling growth, dry weight and other vigour parameters in all the varieties. However, ageing was more pronounced in sponge gourd seeds, twice as that of non-aged seeds. The decline in germination during accelerated ageing was related to the initial degree of deterioration of the seed lot. Percentage of electrolyte leakage increased steadily during the course of ageing and irrespective of the varieties. The EC values of the sponge gourd seeds were high as compared with those of bottle gourd and round melon seeds after 24 hours of soaking which confirms the changes in the membrane permeability.